Criminal law : the basics - Herring, Jonathan (Abingdon, Oxon ; New York, NY : Routledge, 2022)
Criminal Law: The Basics is an insightful introduction to the legal aspects of criminal acts, ranging from battery to burglary and harassment to homicide. Starting with an in-depth exploration of the very concept of crime, the book considers key questions such as: How should we decide what is criminal and what isn't? What is the difference between murder and manslaughter? Could you ever be guilty of stealing your own property? What defences are available to those accused of crime? Featuring a range of case studies, from the infamous to the bizarre, the new edition has been thoroughly updated to include new material on loss of control, accessorial liability, dishonesty, causation, liability, manslaughter and sexual offences. Relevant cases, statutes and suggestions for further reading are included throughout, making Criminal Law: The Basics the ideal starting point for anyone studying this area for the first time.
OCLC-licensed vendor bibliographic record.
Keywords: Criminal law -- Great Britain; Criminal law -- England; Criminal law -- Wales; LAW / General; LAW / Criminal Law / General